Between Two Systems: Reflective insight of private healthcare in India vs the NHS - Natarajan, Lavanya (Advanced Journal of Professional Practice, 2025)
This reflective article offers a personal, first-hand perspective and insight into emergency care within a private, low resource Indian hospital, highlighting structural, clinical and ethical contrasts with the National Health Service (NHS). It emphasises the impact of healthcare system design on patient outcomes, contributing to global health understanding and informing culturally competent, equitable and adaptable future medical care.